Effect of sowing date and sulphur levels on growth and yield of garlic (Allium sativum) (Current Horticulture, 2024)
A field experiment was conducted to find out the suitable sowing date and optimum dose of sulphur to obtain quality yield of garlic (Allium sativum L.) at the SKN College of Agriculture, Jobner, during rabi season of 2014-15. Sixteen treatment combinations with four dates of sowing, viz. 10 October (D1), 25 October (D2), 10 November (D3) and 25 November (D4) and four levels of sulphur (control, 30, 60 and 90 kg/ ha) were taken. Sowing of garlic crop on 25 October along with application of sulphur @ 90 kg/ha significantly increased polar diameter of bulb, average weight of bulb and yield. It may be concluded that most suitable time for sowing of garlic crop is 25 October and a dose of 90 kg/ha sulphur as good for more yield and net returns under semi-arid region of Rajasthan.
Keywords: Sowing dates; Sulphur content; Bulb yield; Cloves; Polar diameter; Semi-arid